Metagenomics-Based Cloning of Amilase-Encoding Genes from the Uncultured Symbiotic Bacteria of a Marine Sponge Theonella swinhoei from Kapoposang Island, South Sulawesi - Priyono, Franciscus Edi; Zilda, Dewi Seswita; Kusnadi, Yudi; Hadi, Tri A; Nurrachmi, Irvina; Uria, Agustinus Robert (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2017)
Marine sponges have recently been recognized as the source ofenzymes, including members of hydrolases. Hydrolytic enzymes are extracellularly produced by sponge-associated bacteria to mediate the metabolism of complex organic matters, thereby assisting the sponge hosts in nutrition and metabolic processes. Among hydrolytic enzymes, amilaseshas attracted increasing attention due to their potential industrial applications. This research work was aimed atutilizing functional metagenomicsapproach for the discovery of amilases derived from the uncultured symbiotic bacteriaof the Indonesian marine sponge Theonella swinhoei. Weinitially constructed a small-insert metagenomiclibrary in Escherichia coliby cloning of metagenome in the size range of5-20 kb prepared from the spongeâs microbiome. Further functional screening of the resulting metagenomic library led to the isolation of two recombinant E. coli clones potentially harboring amilase genes, as indicated by the presence of clearing zones surroinding the selective medium containing 1% amilum.Â